Prospects for the modernization of PJSC “Zaporizhstal” to expand the green steel range of specialized grades - Tymoshenko, D. O.; Kukhar, V. V.; Кухар, В. В.; Тимошенко, Д. О. (Національний університет «Запорізька політехніка», 2025)
Metals and alloys are critical for modern industry, with steel as the most widely used structural material in construction, engineering, energy, and transportation. However, steel production is energy-intensive and environmentally impactful, necessitating technological advancements. Green metallurgy aims to optimize steelmaking processes, reducing emissions and enhancing energy efficiency.